Environmental Assessment & Rating – Have We Lost The Plot?. (2017) - Howard, Nigel
Abstract: This paper asks whether after 20years of development, the new discipline of environmental impact assessment and rating has lost its way. The paper shows examples of problems in building environmental rating systems, and corrupted science in Life Cycle Assessment (LCA), Ecolabelling and Environmental Product Declarations (EPD). Comparisons are drawn with carbon accounting and the problems this will cause for government policies aimed at mitigating climate change internationally. The author speculates on possible causes and provides contrasting examples of initiatives that are trying to produce truly credible, scientifically robust outcomes but struggling to find acceptance. The author concludes with suggestions that might tip environmental impact practice back to legitimacy and relevance.